2015
DOI: 10.3390/md13052559
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effects of the Marine-Derived Compound Excavatolide B Isolated from the Culture-Type Formosan Gorgonian Briareum excavatum

Abstract: In recent years, several marine-derived compounds have been clinically evaluated. Diterpenes are secondary metabolites from soft coral that exhibit anti-inflammatory, anti-tumor and cytotoxic activities. In the present study, we isolated a natural diterpene product, excavatolide B, from cultured Formosan gorgonian Briareum excavatum and investigated its anti-inflammatory activities. We found that excavatolide B significantly inhibited the mRNA expression of the proinflammatory mediators, inducible nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…889 Excavatolide B, a briarane diterpenoid originally isolated from Briareum excavatum, exhibits anti-inammatory and analgesic effects in vitro and in in vivo models. 890 Two sesquiterpenes, (Z,E) and (E,E)-germacrones, constituents of the gorgonian Phyllogorgia dilatata, are odiferous volatiles with fragrant, marine and slightly woody odours with citrus aspects. 891 Finally, amphidinolide P, originally reported from the marine dinoagellate Amphidinium sp., was isolated from the octocoral Stragulum bicolor and also in its predator, the nudibranch Marionia limceana.…”
Section: Cnidariansmentioning
confidence: 99%
“…889 Excavatolide B, a briarane diterpenoid originally isolated from Briareum excavatum, exhibits anti-inammatory and analgesic effects in vitro and in in vivo models. 890 Two sesquiterpenes, (Z,E) and (E,E)-germacrones, constituents of the gorgonian Phyllogorgia dilatata, are odiferous volatiles with fragrant, marine and slightly woody odours with citrus aspects. 891 Finally, amphidinolide P, originally reported from the marine dinoagellate Amphidinium sp., was isolated from the octocoral Stragulum bicolor and also in its predator, the nudibranch Marionia limceana.…”
Section: Cnidariansmentioning
confidence: 99%
“…To determine cell death induced by Exc.B is a consequence of the oxidative stress, ROS production (Zerin et al, ) and nitrite production (Krishnaswamy et al, ) was evaluated, which are thought to play an important role in human carcinogenesis. Diterpenes are secondary metabolites from soft coral that exhibit anti‐inflammatory, anti‐tumor and cytotoxic activities (Lin et al, ). Our results demonstrated that treatment with 60 and 80 µM of Exc.B significantly increased ROS production in A549 cells [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds derived from sponges, algae, mollusks, and other marine organisms are being tested for their therapeutic effects against cancer, anti‐inflammatory, anti‐viral activities, as well as immune modulation and analgesic agents (Amador et al, ; Newman and Cragg, ; Butler, ; Dyshlovoy and Honecker, ). Gyrosanols A and B isolated from soft coral Sinularia gyrosa exhibited anti‐inflammatory activity against RAW 264.7 macrophages by reducing the COX‐2 protein levels (Cheng et al, ) and Excavatolide B (Exc.B) a diterpenoid compound isolated from Briareum excavatum significantly inhibited the mRNA expression of the proinflammatory mediators, inducible nitric oxide synthase (iNOS) and cyclooxygenase‐2 (COX‐2), and in lipopolysaccharide (LPS)‐challenged murine macrophages (RAW 264.7) (Lin et al, ). It seems to be worth for developing as a small molecule drug of curing cancer from natural marine source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrageenan has been widely used as a tool in the screening of novel antiinflammatory drugs [364]. Among others, Porphyra vietnamensis [365,366], Eucheuma Cottonii [367], Dichotomaria obtusata ( Figure 17) [368], Cystoseira sedoides, Cladostephus spongiosis, Padina pavonica ( Figure 18) [369], Ecklonia cava (due to phlorotannins) [370][371][372], Caulerpa racemose [373], Sarcodia ceylanica [374], actinotrichia fragilis [375], Dictyota menstrualis ( Figure 19) [376], Gracilaria cornea [377], Gracilaria birdiae [378], Class Phaeophyceae, Rhodophyceae and Chlorophyceae [379], Caulerpa curpressoides [380,381], Ulva lactuca ( Figure 20) [382], Sargassum wightii and Halophila ovalis [383], Grateloupia lanceolate [384], Sargassum fulvellum and Sargassum thunbergii [385], Briareum excavatum [386], Caulerpa racemose [387], Sargassum hemiphyllum [388], Laurencia obtusa [389], Caulerpa kempfii [390] Caulerpa cupressoides [391] are reported for their analgesic and anti-inflammatory properties.…”
Section: Analgesic and Anti-inflammatory Potentialmentioning
confidence: 99%